Enabling tools for engineering collagenous tissues integrating bioreactors, intravital imaging, and biomechanical modeling - Niklason, Laura E. (National Academy of Sciences, 2010)
Many investigators have engineered diverse connective tissues having good mechanical properties, yet few tools enable a global understanding of the associated formation of collagen fibers, the primary determinant of connective tissue stiffness. Toward this end, we developed a biomechanical model for collagenous tissues grown on polymer scaffolds that accounts for the kinetics of polymer degradation as well as the synthesis and degradation of multiple families of collagen fibers in response to cyclic strains imparted in a bioreactor. The model predicted well both overall thickness and stress-stretch relationships for tubular engineered vessels cultured for 8 weeks, and suggested that a steady state had not yet been reached. To facilitate future refinements of the model, we also developed bioreactors that enable intravital nonlinear optical microscopic imaging. Using these tools, we found that collagen fiber alignment was driven strongly by nondegraded polymer fibers at early times during culture, with subsequent mechano-stimulated dispersal of fiber orientations as polymer fibers degraded. In summary, mathematical models of growth and remodeling of engineered tissues cultured on polymeric scaffolds can predict evolving tissue morphology and mechanics after long periods of culture, and related empirical observations promise to further our understanding of collagen matrix development in vitro.